(untitled) (Docentes 2.0 Journal, 2023)
The sudden confinement registered worldwide caused radical changes in daily activities, including educational ones; the teaching-learning processes immediately migrated to a virtual modality, which caused confusion and innumerable doubts. Therefore, the objective of this document was to know the perception of students and teachers regarding the teaching-learning process in practical classes and the challenges they faced. The research was approached from the hypothetical deductive method, a pragmatic paradigm with a mixed approach of exploratory and cross-sectional design; the population that was selected were the teachers and students of the gastronomy degree of the Tecnológico de Estudios Superiores de Huixquilucan. The results showed various problems, including sharing spaces, investing in equipment, and lack of internet. This result shows a greater complexity than just moving from a face-to-face model to a virtual one, adding that the practical sessions were made difficult by space, where socioeconomic levels and disparities between the urban-rural are part of the problem. It is necessary to rethink the educational processes regarding teaching-learning, especially in the sessions that occupy practical elements, such as cooking classes, derived from the deficiencies observed when returning to the classroom.